2005
DOI: 10.1111/j.1467-6486.2005.00488.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Institutional Reforms on Characteristics and Survival of Foreign Subsidiaries in Emerging Economies*

Abstract:  This study goes beyond the conventional notion of the institutional environment of emerging economies and investigates their dynamic context. It examines the complex influences of policy reforms on the characteristics and survival of foreign subsidiaries in emerging economies before and after the 1997 Asian Economic Crisis. This study proposes that FDI policy reforms during times of crisis may not only have a positive effect on institutional munificence for foreign firms, but such drastic reforms may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(91 citation statements)
references
References 66 publications
(110 reference statements)
3
86
2
Order By: Relevance
“…In particular, the resource endowment of the host economy and its institutional framework moderate the characteristics and survival of foreign subsidiaries, especially in emerging economies (Chung & Beamish, 2005;Meyer & Peng, 2005 Davis and Meyer (2004) found that the determinants of whether subsidiaries engage in R&D differ from the determinants of R&D intensity -in particular, that government support impacts subsidiaries' incidence of R&D but not its level, while competitive conditions affect the level but not the incidence. We thus hypothesize that explanatory factors vary in determining whether or not subsidiaries export at all (propensity), and, if they do, how much they export (intensity).…”
Section: Subsidiary-specific Advantagesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the resource endowment of the host economy and its institutional framework moderate the characteristics and survival of foreign subsidiaries, especially in emerging economies (Chung & Beamish, 2005;Meyer & Peng, 2005 Davis and Meyer (2004) found that the determinants of whether subsidiaries engage in R&D differ from the determinants of R&D intensity -in particular, that government support impacts subsidiaries' incidence of R&D but not its level, while competitive conditions affect the level but not the incidence. We thus hypothesize that explanatory factors vary in determining whether or not subsidiaries export at all (propensity), and, if they do, how much they export (intensity).…”
Section: Subsidiary-specific Advantagesmentioning
confidence: 99%
“…The institutional perspective of business strategy emphasizes the institutional framework as a key factor influencing the strategies and operations of foreign investors (Luo & Peng, 1999;Peng, 2003;Chung & Beamish 2005;Narayanan & Fahey, 2005;Meyer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to these advantages, MNEs may be in a better position to compete and to face the obstacles in the market. For example, MNEs may have better access to resources, or the ability to use internal capital markets when faced with financial constraints, and be able to access overseas credit through their parent companies, which allows them to expand their economic activity even in turbulent periods (Desai et al, 2004;Blalock et al, 2005;Chung and Beamish, 2005).…”
Section: Mnes As a Stabilizing Agentmentioning
confidence: 99%
“…This prediction has been refuted by the increasingly voluminous research that draws on the institutionbased view to tackle IB strategy problems in emerging economies. Five years later, in 2005, seven out of eight papers (88%) in the Journal of Management Studies special issue on strategy research in emerging economies, edited by two of the same editors as for the AMJ special issue and two new editors (Wright et al, 2005) (1) business groups (Chang & Hong, 2000;Guillen, 2000;Khanna & Palepu, 2000;Wan, 2005;Yiu, Bruton, & Lu, 2005); (2) privatization (Filatotchev, Buck, & Zhukov, 2000;Uhlenbruck & De Castro, 2000); (3) foreign investment strategies (Child & Tsai, 2005;Chung & Beamish, 2005;Delios & Henisz, 2000;Hitt et al, 2000;Isobe, Makino, & Montgomery, 2000;Meyer & Nguyen, 2005); (4) domestic strategies in emerging economies (Peng & Luo, 2000;White, 2000); and (5) internationalization strategies for firms based in emerging economies expanding abroad (Brouthers, O'Donnell, & Hadjimarcou, 2005).…”
Section: Introductionmentioning
confidence: 99%